The Philosophy of the Game in the American Ludic Novels of Pre-Digital and Digital Era - Lavrentev, A.I.; Ageeva, M.G. (KnE Social Sciences, 2021)
The Universal Baseball Association, Inc. by R. Coover and Remade by N. Stephenson offer differing views of the evolving concept of “game” in the twentieth and twenty-first centuries. The purpose of the study is to reveal the implications of the game theme in these novels as well as the transformation of the game concept in the twentieth and twenty-first centuries. Coover’s novel analysis in parallel to Kant’s concepts of a man’s ability for reasoning reveals how the imaginary world of the game can become selfsufficient and reduce the creator of the game to no more than one of its participants. Having got out of control the game imposes its own logic on all participants including its creator. It no longer obeys the creators will and the decision center moved to the analogue of Kant’s hypothetical super intelligence phenomenon. Stephenson’s novel offers an example of the gaming reality creation in globalization era. Stephenson’s game presents a dialectical contradiction: it replaces reality but simultaneously serves as a tool for escaping to this reality. Advanced digital technologies create the necessary gaming infrastructure and provide users with the material culture, socio-economic mechanisms for the distribution of online and offline resources, and spiritual culture. This makes the game world as a multidimensional form of reality. The survey has revealed several tendencies of digital technological development such as the set of technological tools available to the designer of the virtual world, the less this game world will differ from authentic reality. In the digital era, the online game becomes a way of active and intensive interaction with the external world rather than an escape from reality. Keywords: game, digital technologies, American literature